Drebrin is a widespread actin-associating protein enriched at junctional plaques, defining a specific microfilament anchorage system in polar epithelial cells - Ludwig-Peitsch, Wiebke; Schnölzer, Martina; Spring, Herbert; Franke, Werner (European journal of cell biology, 2012)
Using immunoblotting, immunprecipitation with subsequent fragment mass spectrometry, and immunolocalization techniques, we have detected the actin-binding ca. 120-kDa protein drebrin, originally identified in - and thought to be specific for - neuronal cells, in diverse kinds of human and bovine nonneuronal cells. Drebrin has been found in numerous cell culture lines and in many tissues of epithelial, endothelial, smooth muscle and neural origin but not in, for example, cardiac, skeletal and certain types of smooth muscle cells, in hepatocytes and in the human epithelium-derived cell culture line A-431. By double-label fluorescence microscopy we have found drebrin enriched in actin microfilament bundles associated with plaques of cell-cell contact sites representing adhering junctions. These drebrin-positive, adhering junction-associated bundles, however, are not identical with the vinculin-containing, junction-attached bundles, and in the same cell both subtypes of microfilament-anchoring plaques are readily distinguished by immunolocalization comparing drebrin and vinculin. The intracellular distribution of the drebrin- and the vinculin-based microfilament systems has been studied in detail by confocal fluorescence laser scanning microscopy in monolayers of the polar epithelial cell lines, MCF-7 and PLC, and drebrin has been found to be totally and selectively absent in the notoriously vinculin-rich focal adhesions. The occurrence and the possible functions of drebrin in non-neuronal cells, notably epithelial cells, and the significance of the existence of two different actin-anchoring junctional plaques is discussed.
Available online 20 February 2012
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 11.02.2021